FOOD SECURITY PROBLEMS IN SUB-SAHARAN AFRICAN COUNTRIES - Grzelak, Aleksander; Sapa, Agnieszka (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
The main purpose of the study is to identify food security problems in Sub-Saharan African countries. Despite progress in increasing food security in the world, it is still one of the most important challenges facing Sub- -Saharan Africa. The research shows that the food security is different across countries. The more favourable situation takes place in South Africa, Botswana, while at the other extreme are countries such as Madagascar, Burundi and Sierra Leone. The economic affordability of food seems to be the most important problem for these countries. So an inclusive growth could be a chance to improve the level of food security.